Pengembangan Bahan Ajar Berbentuk Komik Pada Matapeljaran IPS Materi Kelas IV SDN 1 Jerowaru - Lalu. A. Hery Qusyairi (Pendidikan Al-Gafari, 2024)
Learning media is one component in education that helps determine success in the learning process. So for educators, it is necessary to understand the use of learning media by adjusting the material to be taught. This study aims to develop and determine how students respond to comic-based teaching materials in the social studies subject matter of jobs around me in grade IV of SDN 1 Jerowaru. This type of research is a development using the Borg and Gall model which has been simplified into 7 stages, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial, and 7) product revision. Based on the results of validation by media experts, language experts and education practitioner experts, the results of media validation with an actual score of 34 were categorized as